ANALISIS KATA MAJEMUK BAHASA INDONESIA DALAM PENERJEMAHAN BAHASA INGGRIS - Agustiana, Erika (Lentera: Jurnal Ilmiah Kependidikan, 2016)
A compound verb is made up of two or more words that function as a single verb. A compound verb can be a phrasal verb or a prepositional verb that behaves either lexically or syntactically as a single verb. Compounding or composition is the process of combining two free morphemes into one word and form a new meaning. This compound is different from the phrase. The phrase is a combination of words and formed through a process of syntax. The compound formed a meaning, while the phrase formed more than one meaning. This compound can be divided based on the morphological form and the relationship of the components. Morphologically, compound words are divided into (1) a basic compound word ; (2) a compound word affixed ; and (3) a compound word repeatedly . This compound was a construction line between morphological and syntactic constructions. A compound word is two or more words that have undergone a process of compounding, which then represents a new understanding.